Aplikasi Optimalisasi Muat Barang Dengan Penerapan Algoritma Dynamic Programming Pada Persoalan Integer Knapsack - Daniel Jahja Surjawan; Irene Susanto (Maranatha University Press, 2015)
In the era of globalization, the use of information technology become a necessity that can not be separated in running a business in all instances. The need of information technology is not only used as a supporter of the process, but also has become a major part of which should go well. It was felt also by the CV. Labatrans engaged in courier services, which often occurs excess or shortage even when the goods are loaded into a vehicle that will deliver. There has been no control of the goods to be delivered, so that sometimes exceed the limit load capacity of the vehicle. This cause a heap of goods in the warehouse, and the main problem consumers will be disappointed because the goods delivered are not accepted at the right promised time. Another problem occurs when consumers asked where the goods they are shipped, they want to know where their goods for some reason such as perishable goods or food. And usually the staff of the company can not give an answer because of limited information. The purpose of this research is to create an application that can handle tracking of goods delivered and the load optimization by applying Dynamic Programming Algorithms on the issue of Integer Knapsack